The Effect of Educational Interaction Patterns Between Teacher and Students on the Motivation to Learn Arabic: A Field Study at Al-Falah School - Yulia, Fatma; Ayunda, Annisa (Universitas Yudharta Pasuruan, 2025)
This study aims to analyze the influence of teacher-student interaction patterns on the motivation to learn Arabic among eighth-grade students at MTs Swasta Al-Falah Simpang Kanan, Rokan Hilir, Riau. The main issue addressed in this research is the low learning motivation of students, as indicated by their lack of enthusiasm in Arabic language classes. During the learning process, teachers tended to adopt a formal demeanor and maintain distance from students. This rigid interaction caused students to feel hesitant to participate actively in the learning activities. This research employs a mixed-method approach, combining both quantitative and qualitative methods. The qualitative method was used to gain deeper insight through interviews, which revealed that students are diligent in learning Arabic. Meanwhile, the quantitative method was used to analyze data from a Likert scale questionnaire distributed to 30 students. The instrument was validated using Pearson's product-moment correlation and tested for reliability using Cronbach’s Alpha with the aid of SPSS. Data analysis included normality testing, linearity testing, and simple linear regression analysis. The findings show that the teacher-student interaction pattern has a significant effect on students’ motivation to learn, with a significance value of 0.000 and a regression coefficient of 0.913. This means that every increase in the quality of teacher-student interaction corresponds to a 0.913-point increase in learning motivation. Thus, it is proven that positive and effective interaction between teachers and students can significantly enhance students' motivation to learn Arabic.